Nulidades no processo penal, dignidade humana e segurança jurídica - Siqueira, Daniel Campos Silva de (2019)
The aim of this paper is to analyze what is legal right in order to understand the nullities as a way of defending the order and the procedural subjects. Identifying the concept of law and its founding pillars is a very important matter so as to recognize procedural nullities both in its typical model and in cases where there is misuse of purpose, which is more sensitive and difficult to be proved. To this end, the three fundamental pillars of law, namely law, justice and human dignity are approached. Each of them is central for procedural nullities and only with a close observation of these postulates, the procedure will foster the correct application of the material law and implement the legal certainty expected by all. Thus, human dignity plays a relevant role, since it is assumed, postulated and consequent in the application of law and should always be considered and complied in the interpretation of law. Therefore, it embodies the nature of a supra-constitutional principle. Only in this connection, the justice expected in the solution of every single case will be achieved entailing the necessary legal certainty. This, in turn, will give credibility to the criminal procedure and, ultimately, to the judicial decision. As it should be noted, all subjects involved in the relationship are critical for the nullity topic, since they will practice several acts until the final provision. It is necessary the strict observance of the order, what does not mean excessive formalism but the correct interpretation of the principles and rules that establish the legal action.It must be highlighted that this study does not address kinds of nullities. It examines the general theory and the nullities practiced by the subjects of the legal action both by the non-observance of the typical model – usually pleaded in several procedural douments of prosecution and defense – and in its ideological aspect, characterized by the vice of the misuse of purpose